Pengaruh Berbagai Komposisi Media Tanam Hidroponik Sistem DFT pada Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.) - Nur Hafizah; Farida Adriani; Muhammad Luthfi (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
Lettuce is a type of green leafy vegetable that has many benefits and a good source of vitamins. DFT hydroponics is plant cultivation without using soil. Cocopeat and hydroton are hydroponic growing media. This study aims to (i)determine the effect of various compositions of the DFT hydroponic growing media on growth and yield of lettuce (ii) obtaining the best composition of the DFT hydroponic planting media on growth and yield of lettuce. This study was conducted in Rica Village, Paringin District, Balangan Regency from February to April 2019. This study used a Randomized Design Group (RDG)single factor. The factors observed were the composition of the hydroponic planting media of the DFT system (m) by as much as 5 degrees of consisting of m1 = 100% cocopeat: 0% hydroton (100 g cocopeat: 0 g hydroton), m2 = 0% cocopeat: 100% hydroton (0 g cocopeat: 100 g hydroton) , m3 = 50% cocopeat: 50% hydroton (50 g cocopeat: 50 g hydroton), m4 = 75% cocopeat: 25% hydroton (75 g cocopeat: 25 g hydroton), m5 = 25% cocopeat: 75% hydroton (25 g cocopeat: 75 g hydroton). The results showed that the treatment of the composition of the hydroponic growing media had a very significant effect on plant height 14,21,28 and 35 HST, the effect was very significant on the number of leaves 7,21,28 and 35 HST, significantly affected the wet weight of the plant. The best treatment is obtained at m5 = 25% cocopeat: 75% hydroton (25 g cocopeat: 75 g hydroton).